النقل النهري وتأثيره على قطاع السياحة في مصر خلال القرن التاسع عشر - أبو زيد، أسماء أبو زيد سلامة; شوقي، شروق أسامة; أحمد، نبيل عبدالحميد سيد (جامعة قناة السويس - كلية السياحة والفنادق, 2021)
يحتل النقل مكاناً مهماً وخطيراً في اقتصاديات العالم وحضارته، فهو وسيلة للتبادل التجاري بين الدول، كما أنه يساعد في نقل العلوم والفنون والآداب والنظم السياسية المختلفة، فهو بحق الحلقة التي تربط جهود الجماعات البشرية بعضها ببعض، مهما اختلفت جنسياتها، لغاتها، لونها، عقائدها. فصناعات النقل وإن كانت مرتبطة ارتباطاً وثيقاً بالصناعات المختلفة إلا إنها في الواقع مجموعة مهمة قائمة بذاتها، فكلاً من النقل البري والنهري والبحري والجوي صناعة بها مميزاتها الخاصة في وسائط النقل وأساليبه. فالنقل النهري من أهم وسائل النقل في القرن التاسع عشر، حيث أثرت شركات الملاحة النهرية في مصر خلال هذه الفترة على التطور العمراني فظهرت الشركات السياحية والفنادق مما ساعد على تنشيط حركة السياحة ومن هنا جاءت فكرة البحث، فلا شك أن مقياس تقدم أي دولة يقاس بما تتمتع به من ممرات مائية وأنهار داخلية وطرق برية وسواحل بحرية.
Transport occupies an important and dangerous place in the world’s economies and civilization, as it is a means of trade exchange between countries, it also helps in the transfer of sciences, arts, literature and various political systems. Indeed, it is the link that links the efforts of human groups to each other regardless of their different nationalities, languages, color or beliefs. The transport industries, although closely related to the various industries, are in fact an important group on their own. Each of the land, river, sea and air transport industries has its own advantages in the means and methods of transport .River transport was one of the most important means of transportation in the nineteenth century. During this period, river navigation companies in Egypt affected the urban development, so tourism companies and hotels appeared, which helped stimulate the movement of tourism. Hence the idea of research came. There is no doubt that the measure of any country’s progress is measured by what it enjoys. It has waterways, inland rivers, land roads and sea coasts.
Keywords: السياحة المصرية -- النقل النهري -- الرحلات النيلية -- الاقتصاد المصري